Endovascular embolization for basal ganglia and thalamic arteriovenous malformations - Lan, Jing; Ma, Yi-hui; Feng, Yu; Zhang, Ting-Bao; Zhao, Wen-yuan; Chen, Jin-cao (Frontiers in Neurology, 2023)
Basal ganglia and thalamic arteriovenous malformations (AVMs) represent a special subset of malformations. Due to the involvement of vital brain structures and the specifically fine and delicate angioarchitecture of these lesions, it presents unique therapeutic challenges and technical difficulties that require thorough treatment planning, individualized treatment strategies, and advanced techniques for good clinical outcome. In this study, we presented a series of basal ganglia and thalamic AVMs treated by the transarterial or transvenous embolization. Herein, we summarized our treatment experience and clinical outcomes to further evaluate the effectiveness and safety of endovascular embolization for these AVMs as well as the indications, therapy strategies, and techniques of embolization procedures.